2014
DOI: 10.1007/s40093-014-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tendu (Diospyros melanoxylon RoxB.) leaf vermicompost on growth and yield of French bean (Phaseolus vulgaris L.)

Abstract: Background Tendu (Diospyros melanoxylon RoxB.) leaf is widely used in India in the form of wrapper for making a crude smoking stick popularly known as ''Beedi''. Solapur city of Maharashtra state has large number of small beedi making units. Large quantity waste from these industries in the form of trimmed leaf residues is available as feed material for preparation of vermicompost. The present investigations were aimed to study effect of vermicompost prepared from such novel leaf residues as the tendu leaves o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…This might be due to the presence of plant growth inhibitors, acidic pH (5.6) and nutrients in undiluted 100 % PG. In line with this, Kadam and Pathade (2014) also showed the negative effect of higher concentration of vermicompost application on French bean growth compared to lower concentration of compost application. There were no consistent positive results for plant growth improvement on dilution of original organic formulations, except for 100 % PG.…”
Section: Discussionsupporting
confidence: 72%
“…This might be due to the presence of plant growth inhibitors, acidic pH (5.6) and nutrients in undiluted 100 % PG. In line with this, Kadam and Pathade (2014) also showed the negative effect of higher concentration of vermicompost application on French bean growth compared to lower concentration of compost application. There were no consistent positive results for plant growth improvement on dilution of original organic formulations, except for 100 % PG.…”
Section: Discussionsupporting
confidence: 72%
“…In contrast, Zaller (2006) could not determine an effect of foliar application of aqueous vermicompost extracts to different tomato varieties under field conditions, in terms of plant growth and nutrient content. On the other hand, thorough vermicompost studies were found to show increase in fresh and dry weight of the Chard (Aksu et al, 2017), Bean (Kadam and Pathade, 2014) and Lettuce (Adiloğlu et al, 2018) and improvement of yield and clorophyll content in for lettuce (Kibar, 2018). In general, it is seen that Vermicompost forms may exhibit different effects according to plant type, application method and target.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, stimulated seed germination in various plant species such as mung beans (Karmegam et al 1999), tomato plants (Atiyeh et al 2000b;Zaller 2007), petunia (Arancon et al 2008) and pine trees (Lazcano et al, 2010a) kg/da applications with 93.3%. In another study, lettuce, pea, wheat, tomato, cabbage and radish plants and ornamental plants were first germinated in small pots containing vermicompost obtained from animal wastes, and then they were surprised (Edwards et al 1988).…”
Section: Findings and Discussionmentioning
confidence: 99%